REFORMASI PELAYANAN PUBLIK MELALUI TRANSFORMASI SOCIAL ENTREPRENEURSHIP - Anwaruddin, Awang (Jurnal Borneo Administrator, 2007)
The great change in the fields of politics, economy, and technology in the second millenium era has caused ? as indicated by Featherstone (1990), McRae (1996), dan Osborne & Plastrik (1996) ? a long-term economy and governability crisis, especially in developing countries such as Indonesia. Therefore, various strategic efforst should be made by, among others, improving the quality of public service and enhancing the local economy through a model of decentralized government, which last in the recovery of social prosperity in the area. This paper attempts at discussing the concept of social entrepreneurship to the local apparatus as an effort to improve the performance of public service. Twofold objectives could be achieved through the concept: developing the entrepreneurship spirit among the public service apparatus and creating a model of public service oriented to the social needs.  Keywords: public service, social prosperity, social entrepreneurship.